Resiliensi Berhubungan dengan Kualitas Hidup pada Orang dengan HIV/AIDS - I Nyoman Asdiwinata; Ni Ketut Lisnawati; Ni Kadek Sintha Yuliana Sari (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
HIV / AIDS is a chronic disease that can affect all aspects of life of sufferers. People with HIV / AIDS (PLWHA) experience problems both physically and psychologically which lead to the quality of life of the individual, therefore the ability to manage and rise from the various pressures experienced with resilience is needed. Resilience is an effort that is owned by a person to be able to withstand changes, illness conditions or difficulties experienced. Resilience functions to cope with, control and overcome negative experiences in life, so that PLWHA can adapt. this study used a descriptive correlation design with a cross-sectional study. Sampling method was using total sampling obtained 50 samples. The data used are primary data by collecting ODHA in one place and given a questionnaire of relevance and quality of life. Data were analyzed using Rank Spearman test. The results of resilience in PLWHA were 39 people (78%) in the medium category, and the quality of life for PLHIVs was 33 people (66%) with moderate category. Spearman rank test results with a value of α = 0.05, the results obtained p value = 0.00 with value of r = 0.785, which means there is a relationship of resilience with quality of life in people with HIV/AIDS (PLWHA) (p<α) with strong strength and positive correlation direction. In people with HIV/AIDS, it is not only enough to manage, organize themselves so that life goals are achieved, but also the ability to survive and adapt to the stresses experienced so that PLWHA can have a better quality of life.